Design and Calibration of 100‐Mpixel Multi‐Projection 3D Display with an Enhanced Image Quality. Issue 1 (June 2014) - Lee, Jin‐Ho; Kim, Yookyung; Park, Juyong; Nam, Dongkyung; Park, Du‐Sik
Abstract To achieve an enhanced image quality in a 55‐inch, 100‐Mpixel multi‐projection 3D display for the medical and educational applications, the projector configuration design was improved, and the brightness uniformity compensation and real‐time calibration were performed. Maintaining the density of light‐field rays is important for an immersive natural 3D experiences, this 100‐Mpixel multi‐projection display was designed to have the same light‐field density as a 300‐Mpixel multi‐projection display, so we could acquire very smooth motion parallax without discontinuity in the viewing angle of 24°.